Anti-money laundering and anti-terrorism financing act 2001: a comparison between Malaysia and The United Kingdom / Siti Hanim Abdul Hamid, Sumaiyah Kamarudin - Abdul Hamid, Siti Hanim; Kamarudin, Sumaiyah (2011)
This research looks on a comparative study between Malaysia and the UK concerning the issue of money laundering activities in confiscating and managing the illegal proceeds. Money laundering is a practice of disguising the origins of illegally-obtained money by which the proceeds of crime are made to appear legitimate. Apart from looking at the legal provisions, this research will also cover the issue of concealing evidence with multiple techniques advancement and a stricter enforcement method to combat the problem. The comparison study between Malaysia and the UK will be focusing on the establishment of one (1) central agency in confiscating and managing the illegal proceeds. This research will be conducted in a qualitative method with library- based materials, online searching and also series of interviews. Hence, this study will be limited to general comparisons between AMLA 2001 and PoCA 2002, and not to analyze the effectiveness of both acts.